PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA GURU DENGAN KOMITMEN ORGANISASI SEBAGAI MODERATING - Agus Anas Fuadi (STIE AUB Surakarta, 2014)
The aim of this study are to investigate the influence of leadership, organization culture, job satisfaction, to teachers productivity of Muhammadiyah High School 1 Klaten with organization commitment as a moderating variable. The Hypotheses which have been formulated are: there is influence of leadership, organization culture, and job satisfaction, towards organization commitment as a moderating variable to productivity of employees of Muhammadiyah High School 1 Klaten. The research is a survey to employees of Muhammadiyah High School 1 Klaten with 60 teachers as sample. Data have been collected with questionnaires processed with, assumption of regression test, the path analysis, t test, F test and test of R2. The t test result shows that leadership, organization culture, job satisfaction, and organization commitment have influenced to productivity of employees of Muhammadiyah High School 1 Klaten partially. The F test result shows that the leadership, organization culture, job satisfaction, and organization commitment have inluenced to productivity of employees of Muhammadiyah High School 1 Klaten simultaneously. Keyword: leadership, organization culture, job satisfaction, organization commitment and productivity.